A Comprehensive Management of Geriatric Syndrome in Level Two Health Facilities: Comprehensive Management of Geriatric Syndrome in Level Two Health Facilities - Endah, Felia; Ningrum, Putu; Lusiana (Clinical and Research Journal in Internal Medicine, 2024)
Background: The elderly population is increasing every year, especially in developing countries. Geriatric syndrome is a condition where there is a disturbance in the multifactorial system in the elderly due to decreased function. Case: Woman, 85 years old, came with the main complaint of weakness, accompanied by not wanting to eat and drink since 3 days. The patient could not sleep for 2 days, coughed up phlegm since 1 month ago, accompanied by shortness of breath. One week ago the patient complained of liquid bowel movements accompanied by mucus and dregs. The patient has a history of high blood pressure and was diagnosed with stage III heart failure. From physical examination, GCS E4V4M5, blood pressure 130/80, pulse 72x/m, respiration 20x/m, temperature 37 C, oxygen saturation 94%, anemic conjunctiva, rhonchi in both lung fields, epigastric tenderness, non-pitting upper leg edema. Laboratory examination, Hb 8.0 gr/dL on the second day to 6.7 gr/dL, LED 72 mm/hour. AP chest photo shows consolidation in the middle zone of the right lung and left lower zone, increased vascular pattern with chepalization, CTR 72%. The patient was given initial management of 40 mg omeprazole injection and 4 mg ondansetron. Discussion and conclusion: Based on the results of the anamnesis, physical examination, and support examination, the patient's complaints constitute a geriatric syndrome. The management provided includes medical management to deal with systemic complaints as well as educating the family about the patient's condition. Keywords: Elderly, geriatric syndrome